2019
DOI: 10.3390/jfmk4010013
|View full text |Cite
|
Sign up to set email alerts
|

Organized Sports and Physical Activities as Sole Influencers of Fitness: The Homeschool Population

Abstract: Homeschool children may rely solely on organized sports and physical activities to achieve recommended levels of physical activity and fitness. The purpose of this study was to investigate differences in fitness levels between homeschool children who did, and did not, participate in organized sports or physical activities, and then examine relationships between hours per week in sports or physical activities and cardiorespiratory fitness as measured by portions of the FitnessGram ® test battery. Organized spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 28 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…Finally, the role of extra‐curricular activities on homeschooled students' PA compared to public/private school students needs further research. One study reported that homeschool students who participated in organized sports and PA did not have higher levels of physical fitness or cardiorespiratory fitness compared to homeschool students who did not participate in these activities 21 . Together these results suggest future research into homeschool PA consider the domains of PA related to the structure of the school day, social and environmental PA supports, and PA accrued outside of school hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the role of extra‐curricular activities on homeschooled students' PA compared to public/private school students needs further research. One study reported that homeschool students who participated in organized sports and PA did not have higher levels of physical fitness or cardiorespiratory fitness compared to homeschool students who did not participate in these activities 21 . Together these results suggest future research into homeschool PA consider the domains of PA related to the structure of the school day, social and environmental PA supports, and PA accrued outside of school hours.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found no difference in cardiorespiratory fitness, but did find that elementary‐level homeschool students had less lower abdominal and upper body strength and endurance compared to public school students 27 . Finally, homeschool students who participated in organized sports and PA did not have higher levels of physical fitness or cardiorespiratory fitness compared to homeschool students who did not participate in these activities 21 . These mixed results highlight the need for greater efforts to measure homeschool students' PA to determine if interventions are needed to address PA levels in this growing student population 5…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Engagement in OS does not guarantee that all individuals will achieve health-related benefits such as muscular strength and flexibility, since some OS programs might not provide PA at the frequency and duration necessary to enhance HRF in youth. [20][21][22] Frequency and duration of OS should be considered when examining the health-related benefits of OS. [22][23][24] Previous studies 25,26 have reported some OS programs offer practice only once per week, with a duration of less than 1 hour per session.…”
Section: Introductionmentioning
confidence: 99%
“…While many homeschool families may choose to enroll their child in organized sports or other paid physical activity, this participation alone may be insufficient to improve physical fitness or meet the recommended amounts of physical activity. 8 On the other hand, youth schooled at home may also have increased opportunities for physical activity and free play due to greater amounts of unstructured time. This lack of supervised movement and nutrition along with increased free time creates the potential for changes in the health-related physical fitness and physical activity of this population.…”
mentioning
confidence: 99%